Cryptocurrency Trading and Associated Mental Health Factors: A Scoping Review - Lakshit Jain; Luis Velez-Figueroa; Surya Karlapati; Mary Forand; Rizwan Ahmed; Zouina Sarfraz (Journal of Primary Care & Community Health)
Background: Cryptocurrency trading seemingly mirrors the high-risk, high-reward nature of gambling, and may cause significant psychological challenges to traders. As cryptocurrency trading becomes mainstream, this scoping review aims to synthesize evidence from empirical studies to understand the emotional, cognitive, and social influences on cryptocurrency traders, and identify associated mental health traits/attributes influencing their behaviors. Methods: This review adhered to PRISMA-ScR guidelines, pooling in 13 studies involving 11,177 participants across multiple countries. A detailed literature search was conducted up to August 4, 2024, and was rerun on October 9, 2024 using databases including PubMed/Medline, Web of Science, Embase, and Scopus. Keywords used included psychiatry, psychology, mental health, cryptocurrency, trading behavior, mental health, substance use, gambling, investment, and/or emotional impact. These terms were refined through iterative searches to retrieve the most relevant studies. Results: The scoping review found several key psychological factors affecting cryptocurrency trading behaviors. Many traders exhibited addiction-like behaviors, compulsively trading even when it leads to financial losses. Social media was found to have a strong influence, encouraging herd behavior and impulsive decision-making to follow trends. High levels of psychological distress, including anxiety and depression, were found to be linked to the market’s volatility and risks. Overconfidence bias was observed to make traders underestimate risks and overestimate their ability to predict the market. Cognitive biases like confirmation bias and the disposition effect caused traders to hold onto losing investments and sell winning ones too early. Conclusion: Due to the shared psychological traits between cryptocurrency trading and gambling, it is imperative to implement targeted early interventions to mitigate the risk of its progression into a pathological condition. Tools like the Problematic Cryptocurrency Trading Scale may help identify and manage risky behaviors. Ongoing research is crucial to identify both positive and negative impact of cryptocurrency trading to develop effective support systems and regulatory policies to address traders’ mental well-being.